2011
DOI: 10.1007/s11104-011-0919-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential superoxide dismutase expression in ryegrass cultivars in response to short term aluminium stress

Abstract: Background and aims Aluminium (Al) toxicity limits pasture production in acidic soils, and there is evidence that antioxidant enzymes such as superoxide dismutase (SOD) play a key role against Al-induced oxidative stress. We have investigated (i) the relationship between Al-toxicity and oxidative damage as well as the time-course of SOD activity and (ii) the expression profiles of two SOD isoforms in the roots of two ryegrass cultivars. Methods Jumbo (Al-sensitive) and Nui (Al-semi-tolerant) ryegrass cultivars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 44 publications
(62 reference statements)
3
20
0
4
Order By: Relevance
“…Manganese toxicity may depress photosynthesis as well as the uptake, translocation and utilization of other mineral elements (Ryan and Delhaize 2010). In addition, numerous studies have shown that Al and Mn toxicities can also induce the formation of reactive oxygen species (ROS), and thus trigger oxidative stress in plants (Darkó et al 2004;Mora et al 2009;Cartes et al 2012;Ribera et al 2013).…”
Section: Aluminium and Manganese Toxicitiesmentioning
confidence: 99%
“…Manganese toxicity may depress photosynthesis as well as the uptake, translocation and utilization of other mineral elements (Ryan and Delhaize 2010). In addition, numerous studies have shown that Al and Mn toxicities can also induce the formation of reactive oxygen species (ROS), and thus trigger oxidative stress in plants (Darkó et al 2004;Mora et al 2009;Cartes et al 2012;Ribera et al 2013).…”
Section: Aluminium and Manganese Toxicitiesmentioning
confidence: 99%
“…; Cartes et al . ). Similar results were found in T. aestivum , but no differences were observed between sensitive and tolerant cultivars (Nasr et al .…”
Section: Discussionmentioning
confidence: 97%
“…SOD isoforms were up‐regulated over a longer period in sensitive Nui compared with semi‐tolerant Jumbo, leading finally to increased protection in roots against short‐term Al toxicity (Cartes et al . ). Moreover, using oligonucleotide microarrays in Medicago truncatula , Chandran et al .…”
Section: Discussionmentioning
confidence: 97%
“…To measure concentrations of H 2 O 2 in leaf tissue, the Amplex ® Red Hydrogen Peroxide/Peroxidase Assay Kit (Invitrogen) was used according to the protocol supplied. Superoxide dismutase (SOD) activity was measured as described in Cartes et al (2012), and quercetin glycoside content determined as described in Ballizany et al (2012).…”
Section: Biochemical Assaysmentioning
confidence: 99%